SPECIAL ISSUE ON GLOBAL RESEARCH TRENDS IN MULTIDISCIPLINARY AND INTERDISCIPLINARY STUDIES - Jibril, Abdulaziz Nuhu; Mokshagundam, S. Sriranjani; Moustafa, Mohamed Abdel Fattah Ashabrawy; Paul, Neelam; Sharma, Vaasawa (ShodhKosh: Journal of Visual and Performing Arts, 2026)
ShodhKosh invites original research papers, review articles, and scholarly contributions for a Special Issue on “Global Research Trends in Multidisciplinary and Interdisciplinary Studies.” This issue aims to explore emerging global research trends that connect diverse disciplines, methods, and practices. It welcomes analytical, theoretical, empirical, and practice-based studies on knowledge production, digital transformation, education, culture, sustainability, technology, leadership, entrepreneurship, and human-centered development. Emphasizing collaborative and integrative research, the Special Issue seeks contributions that demonstrate scholarly rigor, innovation, and critical engagement with contemporary global challenges across multidisciplinary and interdisciplinary fields. Issue Editor: Dr. Abdulaziz Nuhu Jibril Department of Agricultural and Environmental Engineering, Faculty of Engineering, Bayero University Kano, Nigeria Email: abdul3787@yahoo.com Dr. S. Sriranjani Mokshagundam Professor, Department of Management, BGS B-School, Bangalore, Karnataka, India Email: Mokshagundam89@gmail.com Mohamed Abdel Fattah Ashabrawy Moustafa Assistant Professor Computer Science, Community College, Prince Sattam Bin AbdulAizi University ALkharj, KSA Email: ashabrawy11@hotmail.com Dr. Neelam Paul Associate Professor and Chairperson, Department of Music, Panjab University, Chandigarh, India Email: drneelampaul2010@gmail.com Prof. Vaasawa Sharma Assistant Professor, School of Law, Starex University, Gurugram, India Email: vaasu0044@gmail.com